Participatory appraisal for healthcare and welfare management strategies of donkeys (Equus ascinus) in Balochistan, Pakistan - Kamran, Kashif; Akbar, Ali; Naseem, Mahrukh; Samad, Abdul; Samiullah,; Achakzai, Jahangir Khan; Rehman, Zia Ur; Sohail Sajid, Muhammad; Ali, Abid (Frontiers in Veterinary Science, 2022)
In spite of the significant importance of the donkeys (Equus ascinus) as draught animal in resource-poor countries like Pakistan, they are equines not receiving the appropriate care. They face challenges including injuries, diseases, lack of basic environment and mismanagement by their owners. The present study aims to provide a brief update on the current status of management of healthcare and the welfare of domestic donkeys using participatory epidemiological tools. These tools can help to provide better strategies for improving their productivity and inclusion in human society. This study was mainly focused only on donkeys and horses, mules and ponies were excluded from the study. A comprehensive questionnaire was completed by 191 donkey owners, including nine farriers (all men, average age = 38.24 ± 12.43) over a time span from October 2021 to March 2022. Multivariate Odds Ratios (MORs) and 95% confidence intervals were used to assess the predictions of health management and welfare measures for the surveyed donkeys. The most common observed medical problems in donkey health were lameness, hyperlipaemia and dental problems. One-third (34.31%) of the donkeys were underweight. The dull donkey with poor appetite needs a clinical emergency owing to a high risk of developing hyperlipemia, which may be life-threatening. These findings are quite useful for the improvement of healthcare management and the welfare of donkeys.